44.3: Enhancing the Performance and Stability of Sky‐bule Perovskite Light‐emitting Diodes with Guanidinium Thiocyanate Additive. (26th August 2021) - Luo, Zhongming; Liu, Baoxing; Luo, Xi; Xu, Ping; Kwok, Hoi-Sing; Li, Guijun
Abstract : Using additives to regulate the morphology of perovskite film is an effective method to enhance the performance of Perovskite Light‐emitting Diodes (PeLEDs). Herein, we propose the strategy of introducing guanidine thiocyanate (GuSCN) additive to improve the crystallinity and reduce the defect density ofthe perovskite film. Compared with the control PLEDs, the PeLEDs added with GuSCN exhibits remarkable external quantum efficiency of 8.62% at 493 nm and a high luminance of 4000 cd/m 2 . Furthermore, the PeLEDs with GuSCN additive shows better stability. The EQE is improved instead of reduced after 30hours storage, and the EL luminescence spectrum shows excellent stability without red shift.